Legal evaluation of the nature of the legislative role of the financial bills proposed by the parliamentary committees in the Iraqi parliament - Badawy, Qasim; Al-Mayahi, Ammar (Journal of Legal Sciences, 2023)
The current research aims to identify the legal evaluation of the nature of the legislative role of the financial bills proposed by the parliamentary committees in the Iraqi parliament، where the problem of research in the tasks of the Iraqi parliament is to monitor the work of the executive authority، either individually or collectively، in order to verify the The extent to which the executive authority properly implements the state’s general policies، and conducts a kind of political control over its work. The importance of research lies in the fact that setting supreme controls in society، such as the right to legislation، is the most important aspect of sovereignty in the state. In the modern state، parliamentary councils enjoy sovereignty according to the theory of the nation’s sovereignty، which makes parliaments an almost absolute legislative authority، bound only by what the constitution restricts them to، which expresses the will of the nation. As well as the comparative approach between laws. The researcher reached a set of the following conclusions and recommendations: Legislative work requires time and depth in research، study and review of the various aspects and implications of the subject Parliamentary committees have become، as a result of practical necessities، and in response to the large increase in the preparation of important legislation for the modern state. Granting some powers to the President of the Republic، represented by the executive authority، in order to create a balance between the two heads of the executive authority We suggest reducing the number of parliamentary committees، as an increase in the number of these committees reduces their effectiveness، and the large number of them leads to a conflict between these committees on the subject of jurisdiction.